Pemberdayaan Masyarakat dengan Pendekatan Triple Helix untuk Pengembangan Kompetensi Wirausaha Masyarakat Desa Mandiri Energi - Utami, Hamidah Nayati; Sandra, Sandra; Ruhana, Ika (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2019)
Community empowerment with the triple helix approach is a community empowerment method that involves three actors, namely: universities, companies and government. Collaboration carried out by the three actors is carried out simultaneously which maintains a balance of shared roles. The purpose of this study is to explain and analyze the implementation of Community Empowerment in Bendosari Energy Independent Village, Pujon Subdistrict with the Triple Helix approach which is carried out by universities, companies and government to develop community entrepreneurship competencies based on local wisdom. The results of this study indicate that community empowerment in Bendosari Village conducted by the three actors is directed to improve community welfare. Empowerment activities are grouped in the fields of infrastructure, community capacity building in the entrepreneurship of local agricultural products and tourism, and the social institutions of rural communities.